Monitoring sport performance in handball - Skarbalius, A. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The aim of this study is to give key indicators of the model of monitoring sport performance in handball. Tendency of body size, age, sporting experience and sport performance in elite men`s handball, sport contest model are considered as the selected key indicators and might be used as a tool for targeting training handball players.